SOIL FERTILITY STATUS AS INFLUENCED BY CROPPING SYSTEM IN EASTERN DRY ZONE OF KOLAR DISTRICT IN KARNATAKA - S, ANIL KUMAR (Innovare Journal of Agricultural Sciences, 2024)
The current investigation was carried out to determine how farming systems under rainfed and irrigated conditions affected the soil’s fertility. Thimmasandra of Bangarpet Taluka, Yadahalli of Kolar Taluka, Gaddur of Mulbagal Taluka, Thippasandra of Malur Taluka, and Kadudevandahalli of Srinivaspurua Taluka were the four villages from where the soil samples (0–15 cm) were gather. As a consequence of chemical examination, the samples’ pH and electrical conductivity were found to be between 5.8 and 7.5 and below 0.4 and 08 dS/m, respectively. The percentage of soil organic carbon in soil samples from irrigated systems was higher than that of rainfed systems, where no soil sample fell into this group. In a similar vein, soils from tomato other vegetable-based cropping systems (irrigated) have lower accessible N, P, K, and Diethylene Triamine Penta Acetic acid extractable Zn, Cu, Mn, and Fe than soils from finger millet-fallow systems (rainfed).